Effectiveness of Employee Performance at the Medan City Regional Development Planning Agency - Zuhro Amini Kamil Tanjung; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This research is a descriptive research that focuses on the effectiveness of employee performance at the Bappeda office in Medan City. This study aims to determine the effectiveness of employee performance at the Regional Development Planning Agency (Bappeda) Medan City. The effectiveness of employee performance at Bappeda Medan City is measured by 4 indicators, namely quality of work, timeliness of completion of work, good cooperation, and communication skills. The data is sourced directly from the Bappeda of Medan City and is of the secondary data type. Quantitative secondary data in question is data on the performance of Bappeda Medan City employees. While the secondary qualitative data in question is a reference to several books that concern and support this research. The results showed that the quality of work, accuracy and discipline in time of completion of work, good cooperation, and communication skills. Of the 4 indicators, all of them have been achieved well so that the performance of employees at the Medan City Bappeda is declared effective.